"Raw, free", and "almost rude": educating warders' children on St Helena Penal Establishment. Issue 1 (6th June 2016) - Brady, Tony James
Abstract : Purpose: – The purpose of this paper is to examine the education of children at St Helena Penal Establishment in Queensland and the trials faced by the educators that delivered their formal schooling. The paper will add to the growing research into the prison island and will provide an insight into a unique facet of education in the newly established Australian State of Queensland. Design/methodology/approach: – The historical analysis draws on original documents and published works to chronicle the provision of education to the children of warders at the St Helena Penal Establishment. Findings: – The establishment of the Department of Public Instruction and the introduction of the State Education Act of 1875 were intended to provide Queensland children from 6 to 12 years of age with free, compulsory, and secular primary education. The full implementation of the Act took until 1900, and in the process, initiatives like St Helena State School No. 12, through issues of administrative control, saw teachers excluded from the Department of Public Instruction in order to include schoolchildren under the auspices of the same department. Research limitations/implications: – The research paper is an initial investigation into the subject and limited by the paucity of primary data available on the topic. Originality/value: – The case study adds to the growing literature on other aspects of the prison at St Helena, Queensland and adds to knowledge of life on the island. Furthermore, the aspects of control over staff on the island and the requirement for the teachers to double as guards, ready to take up arms in defence of the prison, provides new insights into the obligations placed on some early educators.